Evaluation of preoperative predictive factors that determine difficult laparoscopic interval appendectomy - Dogra, Varun; Mushtaq, Umer; Gilkar, Ishfaq Ahmed; Peer, Javid Ahmad (International Surgery Journal, 2022)
Background: Appendicitis is one of the most widely recognised causes of acute abdominal pain. A wide range of treatment from medical management using antibiotics to a minimal invasive surgery can be done for appendicitis. The usual classical open approach of appendectomy is time tested treatment. However laparoscopic appendectomy is being increasingly preferred these days over classical open approach in majority of patients suffering from appendicitis. This study was undertaken to evaluate preoperative data that can serve as predictors of difficult laparoscopic appendectomy and help in planning of surgery. Methods: This was a prospective observational study that was done at department of surgery, government medical college, Srinagar for a period of three years. A total of 50 consecutive patients who underwent laparoscopic interval appendectomy were enrolled in this study. Various preoperative factors such as age, gender, body mass index, history of recurrent episodes, history of previous surgery, ultrasonographic findings and a few investigation results were studied to find their association with the difficulty in performing laparoscopic appendectomy and results were tabulated and analysed. Results: This study found a significant relation between body mass index, history of previous surgery, history of multiple episodes, C reactive proteins and difficulty in doing a laparoscopic interval appendectomy. However, we didn’t find any significant relationship between age, gender, ultrasonographic findings, serum bilirubin, transaminase levels, WBC counts and difficult laparoscopic interval appendectomy. Conclusions: Knowledge of these positive factors for difficult laparoscopic appendectomy could help surgeons during pre-operative assessment and take necessary precautions during laparoscopic appendectomy.